2021
DOI: 10.1002/hyp.14097
|View full text |Cite
|
Sign up to set email alerts
|

Ungaged inflow and loss patterns in urban and agricultural sub‐reaches of the Logan River Observatory

Abstract: Streams in semi-arid urban and agricultural environments are often heavily diverted for anthropogenic purposes. However, they simultaneously receive substantial inflows from a variety of ungaged sources including stormwater returns, tile drainage, and irrigation runoff that help sustain flow during dry periods. Due to the inability to identify sources or directly gage many of these inflows, there is a clear need for methods to understand source origination while quantifying potential gains and losses over high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Such unaccounted for fluxes are common in urban areas throughout the United States (Li et al., 2020). Additional sources of I/I may include net decline of stored groundwater or unaccounted water sources within the catchment such as leakage from water distribution systems and urban irrigation (Bhaskar & Welty, 2012; Bhaskar et al., 2016; Fillo et al., 2021; Lancia et al., 2020; Lerner, 2002; Sanzana et al., 2019; Tennant et al., 2021). There is evidence showing that the groundwater table in urban Milwaukee is dropping over time in recent years (Choi et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Such unaccounted for fluxes are common in urban areas throughout the United States (Li et al., 2020). Additional sources of I/I may include net decline of stored groundwater or unaccounted water sources within the catchment such as leakage from water distribution systems and urban irrigation (Bhaskar & Welty, 2012; Bhaskar et al., 2016; Fillo et al., 2021; Lancia et al., 2020; Lerner, 2002; Sanzana et al., 2019; Tennant et al., 2021). There is evidence showing that the groundwater table in urban Milwaukee is dropping over time in recent years (Choi et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, variants of K-means and other algorithms such as agglomerative hierarchical clustering and fuzzy clustering have been proposed and used in various applications (de Oliveira & Pedrycz, 2007;Jain, 2010;Murtagh & Legendre, 2014;H. Tennant et al, 2021).…”
Section: Clusteringmentioning
confidence: 99%
“…Over the past few decades, variants of K‐means and other algorithms such as agglomerative hierarchical clustering and fuzzy clustering have been proposed and used in various applications (de Oliveira & Pedrycz, 2007; Jain, 2010; Murtagh & Legendre, 2014; H. Tennant et al, 2021). Although clustering is an unsupervised learning technique, it is sometimes used to learn data representation in the pre‐processing step for a supervised learning task.…”
Section: Machine Learning Basicsmentioning
confidence: 99%
“…However, the 2017 flow balance calculations for this reach show a large gain in water (positive %ΔQ) over this section (Figure 2d). More detailed data collection in this reach have shown that these gains can be attributed to multiple, ungaged, surface and subsurface inflows from urban irrigation returns, irrigation distribution systems, and groundwater drains (Buahin et al, 2019;Tennant et al, 2021) that vary in magnitude over time due to changing anthropogenic impacts and hydrologic conditions. These simple net flow balance calculations also provide a foundation to interpret water quality data.…”
Section: Applicationmentioning
confidence: 99%
“…However, within the lower portion of the watershed, there are also many unknown and ungaged inflows that help maintain some amount of flow in the Logan River during these periods. Tennant et al (2021) provide details regarding these influences.…”
Section: Logan River Watershed Descriptionmentioning
confidence: 99%